In the Archives of Marcel Fournier and Marcel Mauss - Marcel Fournier; Şeyda Sevde Tunçbilek (İstanbul Üniversitesi Sosyoloji Dergisi)
Marcel Fournier, born in Quebec in 1945, completed his sociology studies at the University of Montréal and defended his master’s thesis under the supervision of Marcel Rioux at the same university. He came to France to pursue his doctoral study at the École pratique des hautes études under the supervision of Bourdieu. From 1974, when he defended his thesis, he began working at the University of Montréal, where he would spend his entire academic career, in the Department of Sociology. Fournier, who has many publications on sociology of culture, sociology of science and sociological theory, is accepted as the main reference in the field today, especially with his research on the history of French sociology and the Durkheim school. His book Marcel Mauss, published in 1994, is a prosopography that tells the history of both Mauss individually and the Durkheim school. After this biography, Fournier prepared Écrits politiques (1997), a compilation of Mauss’ political writings published in different journals. Lettres à Marcel Mauss, which they edited with Philippe Besnard in 1998, consists of the correspondence between Durkheim and Mauss. Fournier, in collaboration with Jean Terrier, helped to publish Mauss’ unfinished work La nation, ou le sens du social and published Émile Durkheim (1858-1917), the first biography of Durkheim written in French in 2007. Today, it is almost impossible to work in the field of French sociological history without referring to these works, which Fournier personally wrote or edited for publication. This interview, which is the outcome of two meetings held in Paris on 15 and 26 October 2022, proceeds along the line of Durkheim-Mauss-Lévi-Strauss-Bourdieu and, touches on from the story of Mauss’ archive to his personality, political engagement, working method and, of course, his relationship with Durkheim.